If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5x + 8)(7 + x) = 0 Reorder the terms: (8 + 5x)(7 + x) = 0 Multiply (8 + 5x) * (7 + x) (8(7 + x) + 5x * (7 + x)) = 0 ((7 * 8 + x * 8) + 5x * (7 + x)) = 0 ((56 + 8x) + 5x * (7 + x)) = 0 (56 + 8x + (7 * 5x + x * 5x)) = 0 (56 + 8x + (35x + 5x2)) = 0 Combine like terms: 8x + 35x = 43x (56 + 43x + 5x2) = 0 Solving 56 + 43x + 5x2 = 0 Solving for variable 'x'. Factor a trinomial. (7 + x)(8 + 5x) = 0Subproblem 1
Set the factor '(7 + x)' equal to zero and attempt to solve: Simplifying 7 + x = 0 Solving 7 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + x = 0 + -7 x = 0 + -7 Combine like terms: 0 + -7 = -7 x = -7 Simplifying x = -7Subproblem 2
Set the factor '(8 + 5x)' equal to zero and attempt to solve: Simplifying 8 + 5x = 0 Solving 8 + 5x = 0 Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 5x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + 5x = 0 + -8 5x = 0 + -8 Combine like terms: 0 + -8 = -8 5x = -8 Divide each side by '5'. x = -1.6 Simplifying x = -1.6Solution
x = {-7, -1.6}
| 3x-5x+8x=48 | | 5y-y=-16 | | z^10/6 | | 1/3-m/21-1/7 | | -4(7+7x)=-280 | | 3.4-1.08=0.68-5.4x | | 0=2x-x | | -4+6x=4x+16 | | Y-3=-1/3(x-4) | | 14*8*5= | | 3+4y=8y-3 | | 4x^2+3x+42=0 | | n=-3+4x | | -4x+3-3x+2=5x+6 | | 5x+3=69-6x | | x^2-xy-4y^2=-2 | | y+9=5/4 | | X+3=-2x-2 | | Y=2x^2+5x+10 | | Y-6=5(x-3) | | -x+2=-3x+6 | | (13b-7)-4(3b+2)=-7 | | 5y+39x=62 | | 3p+2(p-1)=-2p-4 | | 151=2(45)+2h | | 3x+4y+1=25 | | 3x-2x+x-5x= | | 500(0.08)t=1000 | | z=sqrt(-7+24i) | | 500(0.08)t=1600 | | 4y(2y+7)= | | 4(2x+7)=92 |